Zelda and Ivy : the runaways - Kvasnosky, Laura McGee (Cambridge : Candlewick Press, 2006)
In three short stories, two fox sisters run away from home, bury a time capsule, and take advantage of some creative juice.
K
540
K
Keywords: Foxes -- Fiction; Sisters -- Fiction